EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH DI TPA GUNUNG PANGGUNG KABUPATEN TUBAN - Mayangkara, Agung Prasetya (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
This study aimed to evaluate waste management policy in the Gunung Panggung landfill Tuban Regency with the approach of the five criteria, namely effectiveness, accuracy, adequacy, equity and responsity well as to give advice/recommendations corrective measures to be taken by the Government of Tuban in organizing the waste management in the Gunung Panggung landfill. The method used is descriptive qualitative method. The research object itself is Gunung Panggung Landfill of Tuban Regency as the end point of local government in providing waste management services for the city of Tuban.The results showed that the implementation of waste management at the Gunung Panggung Landfill of Tuban Regency not meet the criteria of accuracy, effectiveness, adequacy, equity and responsitas. This is demonstrated by the performance measurement input selection method that is controlled landfills were not right either the rules or the management of the environment, the low amount of the budget provided for waste management (equivalent to Rp. 950.00/man.month), the limited number of local regulations set to support waste management (only 1 regulations), are still insufficient numbers of technical personnel manager of the landfill, the organizer of the function of institutional forms of waste management is still a part of SKPD lead to less flexible role in the management of budgetary institutions. While the output performance benchmark showed that the waste management policies do not yet meet the criteria of equity, this is evidenced by the low coverage of landfill Mountain Stage (66.73%) and the low awareness of the public to participate in waste management activities, namely awareness to pay a levy of waste (3%) and awareness to waste reduction (27.67%) indicates that the policies implemented have not been responsive to the community.For the Government of Tuban Regency expected to immediately make corrections which are applying the sanitary landfill system by increasing the number of technical personnel manager of the landfill, reviewed the institutional forms and to set local regulations on public participation in waste management. Keywords: Public Policy, Criteria Evaluation and Waste Management